Comparative study of the Spanish and the Japanese legal Systems Regarding liability due to moral damages caused by marital infidelity - Domínguez Yamasaki, María Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
Nowadays, the possibility of determining a liability for moral damages in the field of Family Law is one of the issues which is subject of debate by the doctrine and, as our Supreme Court recognizes, raises the same questions in Comparative Law. Therefore, the subject matter of this paper is a comparison between both Spanish and Japanese legal systems in respect of liability due to moral damages caused by marital infidelity, considering the similarities between both countries’ civil codes in contrast with the opposing solutions given by these countries. The aforementioned similarities bring into light the importance of ethical and moral considerations in order to provide a solution to those cases in which a moral damage is provoked on the occasion of the infringement of the fidelity duty between the spouses
Keywords: liability; moral damages; marital infidelity